MONOPOLY POP-UP MEDIA AS INSTRUCTIONAL INNOVATION FOR GRADE V ELEMENTARY IPAS LEARNING - Vellena Brendawati; Muhammad Khozinul Huda; Susilawati (Jurnal Cakrawala Pendas, 2026)
The low learning outcomes in IPAS at the elementary school level indicate the need for learning media capable of increasing student engagement in the learning process. Although various game-based media have been widely developed, media that integrate the Monopoly game with pop-up visualizations for IPAS learning are still rarely used. This study aims to determine the effect of the Monopop (Monopoly Pop-Up) media on the IPAS learning outcomes of fifth-grade students at SD Negeri 1 Kasugengan Kidul. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design involving 29 students. Data were collected using multiple-choice tests that met validity and reliability criteria and were then analyzed using the Shapiro-Wilk test, the paired-sample t-test, and the N-Gain measure. The results showed a significant difference between learning outcomes before and after the use of the Monopop medium (Sig. = 0.000 < 0.05), with an average N-Gain of 0.6356, which falls into the moderate category. These findings indicate that the Monopop (Monopoly Pop-Up) medium is effective in improving IPAS learning outcomes through more active, interactive, and collaborative learning. The contribution of this study lies in the development of a Game-Based Learning medium that integrates elements of the Monopoly game and pop-up visualizations into a single learning medium. In practice, the Monopop (Monopoly Pop-Up) medium can serve as an alternative for elementary school teachers to support student-centered IPAS learning and create more meaningful learning experiences.